2023
DOI: 10.3390/molecules28020580
|View full text |Cite
|
Sign up to set email alerts
|

Residual Behavior and Dietary Risk Assessment of Chlorfenapyr and Its Metabolites in Radish

Abstract: Chlorfenapyr, as a highly effective and low-toxicity insect growth regulation inhibitor, has been used to control cross-cruciferous vegetable pests. However, the pesticide residue caused by its application threatens human health. In this paper, the residue digestion and final residue of chlorfenapyr in radish were studied in a field experiment. The results of the dynamic digestion test showed that the half-life of chlorfenapyr in radish leaves ranged from 6.0 to 6.4 days, and the digestion rate was fast. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Yilmaz and Balkan tested potatoes for 135 pesticides in a multiresidue assay, and no pesticide residues were found in 93 out of 104 samples, and the other samples in which pesticides were detected had very low residue levels, which is consistent with the results of our study. Sun et al found that the median residue values of chlorfenapyr in radish and radish leaves were 0.12 and 3.92 mg kg –1 for the same duration of treatment (14 days), respectively, and the residue values in radishes were much lower than those in radish leaves . In addition, it may be attributed to microbial degradation in the soil .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yilmaz and Balkan tested potatoes for 135 pesticides in a multiresidue assay, and no pesticide residues were found in 93 out of 104 samples, and the other samples in which pesticides were detected had very low residue levels, which is consistent with the results of our study. Sun et al found that the median residue values of chlorfenapyr in radish and radish leaves were 0.12 and 3.92 mg kg –1 for the same duration of treatment (14 days), respectively, and the residue values in radishes were much lower than those in radish leaves . In addition, it may be attributed to microbial degradation in the soil .…”
Section: Resultsmentioning
confidence: 99%
“…Sun et al found that the median residue values of chlorfenapyr in radish and radish leaves were 0.12 and 3.92 mg kg –1 for the same duration of treatment (14 days), respectively, and the residue values in radishes were much lower than those in radish leaves. 29 In addition, it may be attributed to microbial degradation in the soil. 30 The types and mechanisms of microbial degradation of organophosphorus pesticides were systematically described by Ji et al 31 Degradative strains isolated from pesticide-contaminated soils can utilize organophosphorus pesticides as a carbon and energy source for growth.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, chlorfenapyr was detected in aquatic environments, with sediment concentrations reaching up to 2.03 μg/L, indicating its widespread presence in water systems . In soil, the residual amounts of chlorfenapyr were found to be between 1.35 and 12.25 mg/kg . These findings suggested that chlorfenapyr can enter the environment and potentially pose health risks.…”
Section: Introductionmentioning
confidence: 90%
“…20 In soil, the residual amounts of chlorfenapyr were found to be between 1.35 and 12.25 mg/kg. 21 These findings suggested that chlorfenapyr can enter the environment and potentially pose health risks. Animal studies indicate that chlorfenapyr possesses neuro-and hepatotoxic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Balkan et al tested potato for 135 pesticides in a multi-residue assay, and no pesticide residues were found in 93 out of 104 samples, and the other samples in which pesticides were detected had very low residue levels [29], which is consistent with the results of our study. Sun et al found that the median residue values of chlorfenapyr in radish and radish leaves were 0.12 and 3.92 mg/kg for the same time of treatment (14 days), respectively, and the residue values in radish were much lower than those in radish leaves [30]. In addition, it may be attributed to microbial degradation in the soil [31].…”
Section: Analysis Of Pesticide Residuesmentioning
confidence: 99%